PARTISIPASI UMAT PAROKI SANTO VINCENTIUAS A PAULO SURABAYA DALAM PERAYAAN EKARISTI HARIAN - Purnawati, Purnawati; Ardijanto, Don Bosco Karnan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
This study aims to understand the perspectives of the faithful of Saint Vincentius a Paulo Parish, Surabaya, regarding their participation in daily Eucharistic celebrations and the spiritual fruits they experience through such participation. The study is motivated by various challenges faced by the faithful in participating in daily Eucharistic celebrations, including a lack of interest in attending daily Mass, limited understanding of the Eucharist, the perception that devotional practices are more important than the Eucharist, and the assumption that Eucharistic celebrations are monotonous and less engaging. This research employed a qualitative method and was conducted at Saint Vincentius a Paulo Parish, Surabaya. The participants consisted of eight respondents selected through purposive sampling techniques. Data were collected through observation and direct interviews. The findings reveal that the faithful of Saint Vincentius a Paulo Parish demonstrate a strong commitment to attending and participating in daily Eucharistic celebrations. Their participation provides significant spiritual fruits, particularly in fostering personal spiritual growth and development, as well as bringing positive impacts to their family life.